(untitled) (diségno, 2019)
“To perceive a visual image implies the beholder’s participation in a process of organization. The experience of an image is thus a creative act of integration” (Kepes 1971, p. 17). Thus wrote Gyorgy Kepes in the introduction to his fundamental Language of Vision, to which the fine essay by Andrea Casale, that we present here, certainly owes the clarity of the approach used to examine the theme of the image, not in itself, but as a process, as an act of a discipline of organization of which vision, perception and memory are the protagonists